Manual well drilling investment opportunity in Ethiopia - Weight, Elizabeth; Yoder, R.; Keller, A. (International Water Management Institute, 2013)
Increasing female and male farmers? access to groundwater can contribute to increased incomes, improved food security and improved access to water for livestock and domestic needs. In many contexts, private sector manual well drilling is a reliable and affordable means to access shallow groundwater, but it is not widely available in Ethiopia. Data, information and mapping on pilot manual well drilling efforts in selected areas of Ethiopia indicated that the technique provided affordable access to shallow groundwater for farmers and demonstrated high demand among farmers for manually drilled wells, as well as profitability for drilling businesses. The authors of this paper suggest that investments in creating a spatial database of hydrogeologic suitability domains, investments in driller training, and associated investments in accelerating the drilling industry could catalyze a manual well drilling industry and significantly improve smallholder farmers? affordable access to shallow groundwater.